2016
DOI: 10.5114/pg.2016.57752
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic therapy of oesophageal strictures in children – a multicentre study

Abstract: IntroductionOesophageal strictures are rare in children but may require endoscopic dilation.AimTo gather information on centres performing endoscopic oesophageal dilation in Poland.Material and methodsThe data were obtained from questionnaires concerning the relevant data mailed to 22 paediatric endoscopy centres. Completed questionnaires were received from 11 centres.ResultsIn 2010 the 11 Polish paediatric endoscopy centres performed a total of 10,650 endoscopic procedures. This included 347 oesophageal dilat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 23 publications
1
13
0
Order By: Relevance
“…Previous studies reported successful outcomes approaching 80% in patients with GERD-related strictures. 7 , 11 , 13 In the present study, complete response was achieved in 70% of the cases and satisfactory response in 30%. Eighteen percent of our patients developed strictures secondary to EoE; complete response was achieved in 87.5% of the cases and satisfactory response was achieved in 12.5% cases.…”
Section: Discussionsupporting
confidence: 56%
See 3 more Smart Citations
“…Previous studies reported successful outcomes approaching 80% in patients with GERD-related strictures. 7 , 11 , 13 In the present study, complete response was achieved in 70% of the cases and satisfactory response in 30%. Eighteen percent of our patients developed strictures secondary to EoE; complete response was achieved in 87.5% of the cases and satisfactory response was achieved in 12.5% cases.…”
Section: Discussionsupporting
confidence: 56%
“…6 In a recent multi-center survey that included 106 Polish children with esophageal strictures, post-TEF repair strictures were the most common indication for esophageal dilatation (64%), followed by caustic injury strictures in 16%, then post-inflammatory strictures in 13%. 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most common causes of esophageal stricture in adults are gastroesophageal reflux disease and esophageal cancer. Eighty percent of benign esophageal strictures occur after mucosal injury secondary to chronic acid exposure [1,2]. Pneumatic balloon dilatation is a technique that is used in esophageal strictures, has low complication rates compared to surgical procedures and can be performed more easily and safely [3].…”
Section: Introductionmentioning
confidence: 99%